Differential modulation of the cortical alpha rhythm and activation of distinct neural networks during tactile perception training by learners and non-learners - Saito, Kei; Otsuru, Naofumi; Tateishi, Kaito; Kurebayashi, Ryuji; Onishi, Hideaki (Frontiers in Neuroscience, 2025)
BackgroundThe sensitivity and discrimination capacity of sensory systems can be improved by perceptual training. Most individuals demonstrate tactile perceptual learning, but with marked differences in efficiency. Here, we investigated the neural mechanisms underlying individual differences in tactile learning efficiency at the network level.MethodsElectroencephalographic (EEG) signals were recorded from 25 neurologically healthy participants at baseline, after one training session (50 trials) on the tactile grating orientation discrimination task (GOT), and again after four sessions of GOT training (200 training trials in total). Participants were then divided into low- and high-learning groups based on the post-training change in GOT threshold (sensitivity). Cortical alpha-band power, which is associated with sensory processing efficiency, was compared between baseline and post-training in low- and high-learning groups. Coherence analysis was also performed between EEG electrode pairs to reveal functional connectivity (FC) networks associated with low and high learning.ResultsIn the high-learner group, alpha-band power spectral density (PSD) was significantly stronger post-training at the left central-parietal electrodes. In addition, FC in the alpha band was significantly strengthened within left frontal-parietal regions after training. In the low-learner group, post-training alpha-band PSD was significantly strengthened at the bilateral frontal-central electrodes, while FC in the alpha band did not change significantly compared to baseline.ConclusionThese results suggest that individual differences in tactile learning may result from the utilization of distinct neural networks.